Semiotics of the body, fashion and communication - Martins, Marcelo Machado (2022)
This interview was conducted by the editors of “Revista de Ensino em Artes, Moda e Design”, and answered by Profa. Dra. Ana Claudia Mei Alves de Oliveira and Prof. Dr. Marcelo Machado Martins, on May, 2022; Pacaembu, São Paulo, and Heliópolis, Garanhuns. In it, part of the trajectory of the interviewees at the “Colóquio de Moda” is resumed, with emphasisthe history of the GT that they coordinate, “body, fashion, communication”. Teachers also take stock of the “Colóquio” during the pandemic period of Covid-19, as well as outline future prospects for the insertion of research themes in the GT.